2022
DOI: 10.3389/fimmu.2022.1011279
|View full text |Cite
|
Sign up to set email alerts
|

Central gene transcriptional regulatory networks shaping monocyte development in bone marrow

Abstract: The development of monocytes in bone marrow is a complex process with multiple steps. We used RNA-seq data to analyze the transcriptome profiles in developing stages of monocytes, including hematopoietic stem cells (HSCs), common myeloid progenitors (CMPs), granulocyte–monocyte progenitors (GMPs), and monocytes. We found that genes related to potassium and other cation transmembrane activities and ion binding were upregulated during the differentiation of HSCs into CMPs. Protein transport and membrane surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…We further analyzed the protein processing in ER pathway‐related genes and found that the commonly upregulated genes in Trappc1 cKO naive CD4 + and CD8 + T cells were mainly enriched in ER stress‐related parts. By using gene set enrichment analysis (GSEA) software [38], we found that the positive regulation of response to ER stress pathway was significantly enriched in Trappc1 cKO naive CD4 + and CD8 + T cells (Fig. 3E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further analyzed the protein processing in ER pathway‐related genes and found that the commonly upregulated genes in Trappc1 cKO naive CD4 + and CD8 + T cells were mainly enriched in ER stress‐related parts. By using gene set enrichment analysis (GSEA) software [38], we found that the positive regulation of response to ER stress pathway was significantly enriched in Trappc1 cKO naive CD4 + and CD8 + T cells (Fig. 3E).…”
Section: Resultsmentioning
confidence: 99%
“…The total RNA of the sorted naive CD4 + T cells and naive CD8 + T cells were extracted using TRIzol reagent (Thermo Fisher, 15596018) and sequencing was done by the Annoroad Gene Technology Co., Ltd. (Beijing). Differential expressed genes were carried out by DEseq2 software [38]. KEGG pathway enrichment was performed by KOBAS 3.0.28 (http://kobas.cbi.pku.edu.cn/) [37,59].…”
Section: Rna Sequencing Analysismentioning
confidence: 99%
“… 62 https://cytoscape.org/ STRING11.5 This paper https://cn.string-db.org/cgi/input?sessionId=brxHAcCk07dk&input_page_show_search=on GSEA_4.0.3 Zhang et al. 7 , 63 https://www.gsea-msigdb.org/gsea/index.jsp DESeq23.17 Wang et al. 64 Lei et al.…”
Section: Methodsmentioning
confidence: 99%
“… 2 , 3 Some early progenitors will lose multipotency to adopt a particular fate, while others continue to undergo lineage commitment and differentiation under elegant regulation by transcriptional profiles, growth factors, and cytokines/chemokines. 4 , 5 , 6 , 7 Myeloid hematopoiesis is a finely controlled consecutive developmental process, and the intrinsic molecular mechanisms regulating myelopoiesis remain to be studied. Thus, exploring the carefully regulated molecular network underlying the differentiation of myeloid progenitors into downstream cell subsets is critical to our understanding of the finely orchestrated process of myeloid development during homeostasis and myelopoiesis emergency.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential for transforming monocytes into macrophages in response to inflammatory signals 112 . RNA sequencing data suggested that IRF7 may regulate the transition of granulocyte‐monocyte progenitors (GMPs) into monocytes in both mice and humans 113 . Moreover, IRF7 is activated in inflammatory monocytes and bone marrow‐derived macrophages by TLR2 114 .…”
Section: Signalling Pathway and Biological Function Of Irf7mentioning
confidence: 99%